Environment and Virus Interactions: Towards a Systematic Therapy of SARS-CoV-2 - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2022)
The truth about SARS, why the virus spreads, China’s coverup, how scared should we feel and other details are reported in summary. The main purpose of the paper is to compare the previous coronavirus epidemics with the one occorring since 2019 and to report the main preventions and therapies on the actual problem that is finally approacing the end. Hydrossyclorochine, remdesivir, ivermectin, molnupiravir and other terapeutical drugs are taken in consideration including the monoclonal antibodies. After the mRNA vaccine approach and the vaccines with adenovirus vector, the Novavax and the Valneva are taken in consideration as perspectives.